The territorial expansion of mafia-type organized crime: the case of the Italian mafia in Germany - Sciarrone, Rocco (Crime, law and social change, 2014)
The present paper deals with the territorial movements of the mafia groups. After postulating that the concept of mafia refers to a form of organized crime with certain specific characteristics of its own, the paper presents: i) a repertory of the mechanisms underlying the processes whereby mafias expand beyond their home territories, and ii) a taxonomy of the forms that the mafia assumes in nontraditional territories. In a case study approach, the conceptual framework thus outlined is applied to the mafia’s presence in Germany, as reconstructed from documentary and judicial sources. Though this is an exploratory investigation, certain findings are clear: i) the ‘Ndrangheta is more active in Germany than the other traditional Italian mafias (Cosa Nostra and Camorra), and ii), even in "successful" expansions, the mafia does not reproduce the embeddedness it typically shows in its home territories, but chiefly concentrates on infiltrating the economy and dealing on illegal markets.